2014
DOI: 10.2109/jcersj2.122.237
|View full text |Cite
|
Sign up to set email alerts
|

Development of nano-sized superparamagnetic ferrites having heat generation ability in an AC magnetic field for thermal coagulation therapy

Abstract: Thermal coagulation therapy using powdered magnetic materials in an alternating (AC) magnetic field has been expected as a treatment of cancerous tissues. For nano-sized superparamagnetic particles, the magnetic energy is mainly converted to a heat generation ability by the rotation of the magnetic moment (Néel relaxation) along with the rotation of the particles (Brownian relaxation). Fe 3 O 4 (magnetite) nanoparticles have been mainly investigated as the candidate material for this type of therapy. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Where µ 0 is the permeability of free space, χ // is the AC magnetic susceptibility (imaginary part) [53]. This result underscore the possibility that the magnetic field can be tuned to optimize heating for the application of hyperthermia.…”
Section: Heat Generation Propertiesmentioning
confidence: 92%
“…Where µ 0 is the permeability of free space, χ // is the AC magnetic susceptibility (imaginary part) [53]. This result underscore the possibility that the magnetic field can be tuned to optimize heating for the application of hyperthermia.…”
Section: Heat Generation Propertiesmentioning
confidence: 92%
“…Nishimori et al [ 20 ] reported that YIG MNPs with sizes of 20.5–36.8 nm have a maximum thermal efficiency ( SAR coefficient) at an AC magnetic field with a frequency of 370 kHz and an amplitude of 1.77 kA m −1 . For single‐domain MNPs, Aono [ 21 ] demonstrated experimentally that the thermal efficiency of YIG ferrite materials is the highest compared with the most studied Fe 3 O 4 NPs for single‐domain particles. The high value of the effective constant of magnetic anisotropy for single‐domain magnetic YIG NPs compared with bulk samples (≈2 orders of magnitude) [ 22,23 ] is also a prerequisite for maximum thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Выбор шпинели MgFe 2 O 4 определился тем, что МНЧ ферритов-шпинелей MFe 2 O 4 (M = Mn, Fe, Co, Ni, Cu или Sr) обладают высокой химической стабильностью, низкой токсичностью и магнитной анизотропией, а также возможностями синтеза частиц заданных размеров и температур Кюри [16][17][18][19]. Все это делает МНЧ шпинели MgFe 2 O 4 ниболее перспективными для использования в разнообразных технологических применениях, а также для биомедицины [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionunclassified